2012
DOI: 10.1016/j.bpc.2011.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of NO and O2 transport facilitated by polymerized hemoglobin solutions in an arteriole that takes into account wall shear stress-induced NO production

Abstract: A mathematical model was developed to study nitric oxide (NO) and oxygen (O2) transport in an arteriole and surrounding tissues exposed to a mixture of red blood cells (RBCs) and hemoglobin (Hb)-based O2 carriers (HBOCs). A unique feature of this model is the inclusion of blood vessel wall shear stress-induced production of endothelial-derived NO, which is very sensitive to the viscosity of the RBC and HBOC mixture traversing the blood vessel lumen. Therefore in this study, a series of polymerized bovine Hb (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…However, the effect of wall shear stress changed at small blood vessel diameters. This likely is a result of variations in the RBC free plasma layer and velocity profile blunting that occurs within the simulated arteriole [ 47 , 48 ]. Previous studies have reported that shear stress is a modulator of angiogenesis [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the effect of wall shear stress changed at small blood vessel diameters. This likely is a result of variations in the RBC free plasma layer and velocity profile blunting that occurs within the simulated arteriole [ 47 , 48 ]. Previous studies have reported that shear stress is a modulator of angiogenesis [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, O 2 delivered was mostly a function of blood flow and O 2 affinity for the acellular Hb. O 2 delivery to the tissues following a blood transfusion is significantly inferior to that of an HBOC transfusion, as acellular Hb enhances O 2 transport via facilitated O 2 diffusion of oxygenated-Hb (38, 39). The participation of an HBOC in O 2 delivery depends on the rate of diffusion of O 2 through the Hb solution, which is eightfold compared with plasma.…”
Section: Discussionmentioning
confidence: 99%
“…NO scavenging occurs since oxyHb rapidly and irreversibly reacts with NO, producing oxidized Hb (metHb) and nitrate, a reaction that is normally buffered by the RBC membrane. O 2 oversupply occurs due to radial diffusion of HBOC molecules, as they are less restricted to the center of the vessel, which results in facilitated O 2 transport . Both NO scavenging and oversupply of O 2 cause vasoconstriction and hypertension, which are further exacerbated by the extravasation of acellular Hb into the perivascular space .…”
Section: Introductionmentioning
confidence: 99%
“…O 2 oversupply occurs due to radial diffusion of HBOC molecules, as they are less restricted to the center of the vessel, which results in facilitated O 2 transport. 9 Both NO scavenging and oversupply of O 2 cause vasoconstriction and hypertension, which are further exacerbated by the extravasation of acellular Hb into the perivascular space. 10 The vasoconstriction and hypertension observed with previous generations of HBOCs likely accounted for some of the injury observed in vital organs such as the kidney, liver, and spleen.…”
Section: ■ Introductionmentioning
confidence: 99%